2012
DOI: 10.1128/aac.06258-11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of First-Line Antifungal Agents on the Outcomes and Costs of Candidemia

Abstract: dCandida species are the leading causes of invasive fungal infection among hospitalized patients and are responsible for major economic burdens. The goals of this study were to estimate the costs directly associated with the treatment of candidemia and factors associated with increased costs, as well as the impact of first-line antifungal agents on the outcomes and costs. A retrospective study was conducted in a sample of 199 patients from four university-affiliated tertiary care hospitals in Korea over 1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Our results confirm recent studies’ results, in which a relationship between delaying the initiation of antifungal therapy and mortality was demonstrated [24,49]. For example, Bassetti et al [49] showed that the initiation of antifungal treatment 48 h after having the first positive blood culture report was an independent determinant of hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirm recent studies’ results, in which a relationship between delaying the initiation of antifungal therapy and mortality was demonstrated [24,49]. For example, Bassetti et al [49] showed that the initiation of antifungal treatment 48 h after having the first positive blood culture report was an independent determinant of hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, ICU stay, central venous catheterization, mechanical ventilation, length of hospitalization, number of comorbidities, severe sepsis and septic shock were identified as predictors of mortality in patients with candidemia. These results are in agreement with previously published studies that reported risk factors for mortality in patients with candidemia [4,16,20,28,[31][32][33].…”
Section: Discussionsupporting
confidence: 83%
“…Others showed that inappropriate antifungal treatment prolonged LOS by 8 days, and contributed an extra $13 000 to total costs and increased mortality (28.8% vs 0%) . Therefore choosing an appropriate first‐line antifungal agent is crucial for better outcomes, reduced LOS and lower hospital cost of managing candidiasis …”
Section: Discussionmentioning
confidence: 99%